The structure of the weed and seed productivity of weeds in plantings of willow energy - Makukh , Y.Р. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The structure of the weed and seed productivity of weeds in plantings of willow energy the first year of life. It is established that the greatest number of weed species are presented in families of grass: Graminеае, Chenopodiaceae, Polygonaceae, Solanaceae, Rubiaceae.